Apni Youn Pehechaan Dusro Ko Batana (Hindi) - Prayas Health Group (My University, 2023)
There is a lot of stigma attached to people who come out and talk about their sexuality.This video educates about how when and with whom to share about our gender and sexuality and how this should be normalized.
Keywords: Identifying and Sharing our Gender with others